Notch Signaling in Inflammation-Induced Preterm Labor - Jaiswal, Mukesh K. (Sci Rep, 2015)
Notch signaling plays an important role in regulation of innate immune responses and trophoblast function during pregnancy. To identify the role of Notch signaling in preterm labor, Notch receptors (Notch1-4), its ligands (DLL (Delta-like protein)-1/3/4), Jagged 1/2) and Notch-induced transcription factor Hes1 were assessed during preterm labor. Preterm labor was initiated on gestation day 14.5 by intrauterine (IU) injection of peptidoglycan (PGN) and polyinosinic:cytidylic acid (poly(I:C). Notch1, Notch2, Notch4, DLL-1 and nuclear localization of Hes1 were significantly elevated in uterus and placenta during PGN+poly(I:C)-induced preterm labor. Ex vivo, Gamma secretase inhibitor (GSI) (inhibitor of Notch receptor processing) significantly diminished the PGN+poly(I:C)-induced secretion of M1- and M2-associated cytokines in decidual macrophages, and of proinflammatory cytokines (IFN-γ, TNF-α and IL-6) and chemokines (MIP-1β) in decidual and placental cells. Conversely, angiogenesis factors including Notch ligands Jagged 1/2 and DLL-4 and VEGF were significantly reduced in uterus and placenta during PGN+poly(I:C)-induced preterm labor. In vivo GSI treatment prevents PGN+poly(I:C)-induced preterm delivery by 55.5% and increased the number of live fetuses in-utero significantly compared to respective controls 48 hrs after injections. In summary, Notch signaling is activated during PGN+poly(I:C)-induced preterm labor, resulting in upregulation of pro-inflammatory responses, and its inhibition improves in-utero survival of live fetuses.